Governança dos atores locais em um cluster turístico: a associação de produtores de vinhos finos do vale dos vinhedos (APROVALE) - Xavier, Thiago Reis (2016)
Tourism comprises a set of equipment and services offered that together form the tourism product. Due to complementarity, interdependence and geographic concentration it is possible to understand destinations as clusters, since territorial grouping that characterizes the tourism product. Considering the tourists clusters fragmented composition emerges the actors need to establish collaboration relations and partnerships in interorganizational networks. It should be highlighted that to obtain competitive advantages through networks, the existence of a governance structure capable to organize the relationships between local actors is required, in order to ensure the guarantee of actors collective interests. This study aims to propose a model of analysis of governance in tourism clusters. The specific goals are: (a) test the model proposed it in the coordination structure and mechanisms involved in the Associação dos Produtores de Vinhos Finos do Vale dos Vinhedos - Association of Fine Wine Producers of the Vineyards Valley - (APROVALE) formation; (b) identify the actors which comprise APROVALE s tourist governance structure; (c) describe and analyse APROVALE structure; (d) identify, describe and analyse coordination mechanisms involved in APROVALE governance structure formation; and, (e) identify and analyse institutional arrangement formed from Vineyards Valley tourist governance structure. In order to do so, an exploratory and qualitative case study was suggested. The data was collected from primary and secondary sources. The secondary sources comprised documental/ bibliographic research. The primary sources comprised the non-participant observation and twelve semi-structured interviews with local actors, whereas four are public actors and eight private ones. The data set were analysed through content analyses. From these data, we draw on a research framework from which governance model of analyses in tourist destinations was proposed. The model is structured in the following categories: (1) local context; (2) destination governance structure; (3) destination governance development; (4) destination governance coordination; (5) destination governance results; and (6) institutional arrangement pattern. The results analyses were carried out from the previously established model, through which governance analysis was conducted. The results show that APROVALE is a private association that adopts an administrative structure composed of (a) General Assembly; (b) High Council; (c) Executive Board; (d) Audit Council; and (e) Geographic Indication Technical and Research Indicator Council. The organization has 68 members. The organization has shortage of attractive, entertainment activities, formalized interaction with the government and involvement with society. It should be highlighted that the Association Statute is the instrument which formalize and regulates the organization and members behaviors. Members share resources as wine grapes and wine productions methods. The results indicated: power equality between partners, the existence of high level trust, low incidence of conflict situations and the prioritization of collective interests. APROVALE adopt accountability and transparency mechanisms and provides a set of compensations to its members, such as (a) consolidation of Vineyards Valley as a destination; (b) increasing tourist demand; (c) media (investment) return, and (d) offer qualification. After all, was identified that APROVALE institutional arrangement pattern is enterprise and Network Administrative Organization (NAO). The proposed model presents a number of factors can influence the success of networks and governances to seek qualify a tourism cluster.